2003
DOI: 10.1002/ajim.10164
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of asbestos burden in women with mesothelioma

Abstract: The asbestos body and fiber burden in these cases show variation in tissue burden. Some cases in this study had appreciable burden, which was attributed to secondhand exposure from occupationally exposed family members. Mesothelioma can occur also in individuals with comparatively low tissue burdens of asbestos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…It is probably salient that the size of the asbestos particles reported in the present study is within the range, which constitute fiber burden most readily inhaled into the deeper parts of the respiratory system. Similarly the sizes of asbestos particles found in the present study overlap with the sizes found in the lung tissue of mesothelioma cases [Dodson et al, 2002;Suzuki and Yuen, 2002]. Possibly of more importance is the fact that the sizes of these fibers are consistent with the sizes of asbestos fibers found in areas outside of the lung in those sites where mesothelioma originate [Sebastien et al, 1980;Dodson et al, 1990Dodson et al, , 2000aYuen, 2001, 2002].…”
Section: Discussionsupporting
confidence: 76%
“…It is probably salient that the size of the asbestos particles reported in the present study is within the range, which constitute fiber burden most readily inhaled into the deeper parts of the respiratory system. Similarly the sizes of asbestos particles found in the present study overlap with the sizes found in the lung tissue of mesothelioma cases [Dodson et al, 2002;Suzuki and Yuen, 2002]. Possibly of more importance is the fact that the sizes of these fibers are consistent with the sizes of asbestos fibers found in areas outside of the lung in those sites where mesothelioma originate [Sebastien et al, 1980;Dodson et al, 1990Dodson et al, , 2000aYuen, 2001, 2002].…”
Section: Discussionsupporting
confidence: 76%
“…In the present group, 75% of the cases were positive for amosite, 70% for tremolite, 60% for crocidolite, 55% for anthophyllite, 50% for actinolite, and 40% for chrysotile (Figure 1). A common finding in this group when compared with the fiber burden from two mesothelioma studies (Dodson et al, 1997(Dodson et al, , 2002 is that the exposures, reflected by the tissue burden in each group, often were to mixed types of asbestos. The common finding of amphibole content in these lung cancer cases and cases with mesothelioma (Dodson et al, 1997(Dodson et al, , 2002 seems to offer a contradiction in that the potential for exposure from commercial products should greatly favor chrysotile, since 93% of the world's production for such products has been reported to be this type of asbestos (Champness et al, 1976).…”
Section: Discussionmentioning
confidence: 91%
“…The data must always be reviewed with awareness of what was counted or not counted, the magnification used, and the type of instrument for analysis. Much of the previous data on tissue burden of asbestos bodies and uncoated asbestos fibers was from individuals with mesothelioma (Dodson & Levin, 2001;Churg & Vedal, 1994;Churg et al, 1984;Dufresne et al, 1995;Dodson et al, 2002). This in part is attributable to the fact that mesothelioma is considered as an asbestos marker disease (Craighead et al, 1982), in contrast with lung cancer, which has several causations, including the smoking of cigarettes.…”
mentioning
confidence: 86%
“…Household contact with an asbestos worker is a welldocumented source of asbestos exposure among women (7)(8)(9)(10)(11), but women may also be exposed from environmental or occupational contact. Usually, less than 10% of an asbestos-exposed workforce is female (12).…”
mentioning
confidence: 99%